A zero-dimensional perovskite scintillator material and a zero-dimensional perovskite scintillation screen prepared from the scintillator material
Patent Information
- Application Number
- CN202610811490.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-05
- Publication Date
- 2026-10-13
AI Technical Summary
然而,这类材料易吸水潮解,限制了此类材料在高湿环境下的推广
本发明提供的零维钙钛矿闪烁屏是将闪烁体颗粒以化学键的形式锚定在疏水单体形成的聚合物基质中,增加了所述闪烁屏的水稳定性。所述零维钙钛矿闪烁屏可以解决零维钙钛矿闪烁体在潮湿环境下发光不稳定的痛点。所述零维钙钛矿闪烁屏同仅进行物理互混的样品相比,本发明的零维钙钛矿闪烁屏可以在0-85%的相对湿度下保持初始发光强度24小时不变,且能在水下进行连续24小时的X射线成像。所述零维钙钛矿闪烁屏在潮湿环境和水下稳定发光、成像。
Smart Images

Figure CN122897774A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of X-ray imaging technology, specifically to a zero-dimensional perovskite scintillator material containing polymerizable groups, a zero-dimensional perovskite scintillator screen prepared by copolymerization with hydrophobic monomers, and the preparation methods and uses of both. Background Technology
[0002] Organic-inorganic hybrid zero-dimensional (0D) metal halides possess excellent photophysical properties, low preparation costs, and diverse tunable structures, and are currently widely used in fields such as PLEDs, optical anti-counterfeiting, and X-ray scintillation imaging. However, these materials are prone to hygroscopic deliquescence, which limits their application in high-humidity environments. Summary of the Invention
[0003] To overcome the shortcomings of existing scintillator materials, such as easy water absorption and deliquescence, this invention provides a zero-dimensional perovskite scintillator material containing polymerizable groups, and a zero-dimensional perovskite scintillator screen prepared by copolymerizing the zero-dimensional perovskite scintillator material with hydrophobic monomers. The zero-dimensional perovskite scintillator screen has the characteristics of being able to perform X-ray imaging in high humidity environments and underwater. In particular, under a relative humidity of 0-85%, the zero-dimensional perovskite scintillator screen maintains its initial luminous intensity basically unchanged for 24 hours, and the zero-dimensional perovskite scintillator screen can perform continuous X-ray imaging underwater for 24 hours.
[0004] To achieve the above objectives, the present invention adopts the following technical solution: A zero-dimensional perovskite scintillator material, wherein the general chemical formula of the scintillator material is: A m MX j ; Wherein, A is a cation containing polymerizable groups, and its structural formula is shown in Formula 1 below: Formula 1 In Formula 1, R1, R3, R4, and R5 may be the same or different, and are independently selected from hydrogen and alkyl groups; R2 is -O- or -NH-; n is 1, 2, or 3. X is any one or a combination of Cl, Br, and I; M is any one or a combination of Mn(II), Sb(III), Cd(II), Eu(III), Tb(III), Zn(II), and Zr(II); m and j are both positive integers, and m and j ensure the charge balance of the scintillator material.
[0005] According to an embodiment of the present invention, m is an integer between 1 and 5, j is an integer between 3 and 7, and m and j ensure the charge balance of the scintillator material.
[0006] According to an embodiment of the present invention, m is 2, 3 or 4, and j is 4, 5 or 6.
[0007] According to an embodiment of the present invention, exemplarily, when M is a divalent metal ion, m is 2 and j is 4; or, when M is a divalent metal ion, m is 4 and j is 6.
[0008] According to an embodiment of the present invention, exemplarily, when M is a trivalent metal ion, m is 2 and j is 5; or, when M is a trivalent metal ion, m is 3 and j is 6.
[0009] According to an embodiment of the present invention, in Formula 1, R1, R3, R4, and R5 may be the same or different, and are independently selected from hydrogen, C, and C. 1-5 alkyl.
[0010] According to an embodiment of the present invention, in Formula 1, R1, R3, R4, and R5 may be the same or different, and are independently selected from hydrogen, C, and C. 1-4 alkyl.
[0011] According to an embodiment of the present invention, in Formula 1, R1, R3, R4, and R5 may be the same or different, and are independently selected from hydrogen, C, and C. 1-3 alkyl.
[0012] According to an embodiment of the present invention, in Formula 1, R1, R3, R4, and R5 may be the same or different, and are independently selected from hydrogen, C, and C. 1-2 alkyl.
[0013] According to an embodiment of the present invention, A is one of (alkyl)acrylamidoethyltrialkylammonium and (alkyl)acryloyloxyethyltrialkylammonium.
[0014] According to an embodiment of the present invention, the (alkyl)acrylamidoethyltrialkylammonium is selected from methacrylamidoethyltrimethylammonium; the (alkyl)acryloyloxyethyltrialkylammonium is selected from methacryloyloxyethyltrimethylammonium.
[0015] This invention also provides a method for preparing the above-mentioned scintillator material, comprising the following steps: 1) Dissolve the metal halide salt in a normal solvent to obtain a metal halide salt solution; 2) Add the halide salt corresponding to the cation containing polymerizable groups to the above metal halide salt solution, and precipitate out to obtain a powdery precipitate; or, add the halide salt corresponding to the cation containing polymerizable groups to the above metal halide salt solution, and then add the antisolvent, and precipitate out to obtain a powdery precipitate. 3) The powder precipitate obtained in step 2) is washed with a hydrophobic monomer, centrifuged, and the lower powder solid is collected to obtain the scintillator material.
[0016] According to an embodiment of the present invention, in step 1), the positive solvent is selected from at least one of methanol, ethanol, isopropanol, n-butanol, n-pentanol, isoamyl alcohol, n-hexanol, n-octanol, acetonitrile, dimethyl sulfoxide, and dimethylformamide.
[0017] According to an embodiment of the present invention, in step 1), the metal halide salt is at least one of the chloride of metal M, the bromide of metal M, and the iodide of metal M; wherein M is any one or a combination of several of Mn(II), Sb(III), Cd(II), Eu(III), Tb(III), Zn(II), and Zr(II).
[0018] According to an embodiment of the present invention, preferably, the metal halide salt is at least one of the following: a chloride of metal Mn, a bromide of metal Mn, and an iodide of metal Mn; preferably, the metal halide salt is a chloride of metal Mn, a bromide of metal Mn, and an iodide of metal Mn, wherein the molar ratio of the chloride of metal Mn, the bromide of metal Mn, and the iodide of metal Mn is (0-0.1):(0.95-1.05):(0-0.1).
[0019] According to an embodiment of the present invention, in step 1), the concentration of the metal halide salt solution is 10-50 mmol / L, for example, 10 mmol / L, 15 mmol / L, 20 mmol / L, 25 mmol / L, 30 mmol / L, 35 mmol / L, 40 mmol / L, 45 mmol / L or 50 mmol / L.
[0020] According to an embodiment of the present invention, in step 2), the halide salt corresponding to the cation containing polymerizable groups is preferably the chloride salt corresponding to the cation containing polymerizable groups.
[0021] According to an embodiment of the present invention, in step 2), the halide salt corresponding to the cation containing polymerizable groups can be added in the form of an aqueous solution of the halide salt corresponding to the cation containing polymerizable groups, or it can be added directly in the form of halide salt powder corresponding to the cation containing polymerizable groups.
[0022] According to an embodiment of the present invention, in step 2), the amount of cation A with polymerizable groups in the halide salt corresponding to the cation containing polymerizable groups is m times the amount of metal ion M in the metal halide salt.
[0023] According to an embodiment of the present invention, in step 2), the precipitation time is 0.5-5 hours, preferably 1-3 hours; the precipitation temperature is room temperature.
[0024] According to an embodiment of the present invention, in step 2), the antisolvent is selected from anhydrous diethyl ether.
[0025] According to an embodiment of the present invention, in step 2), the volume ratio of the antisolvent to the normal solvent is 0.5-5:1, for example, 0.5:1, 1:1, 2:1, 3:1, 4:1 or 5:1.
[0026] According to an embodiment of the present invention, in step 3), the hydrophobic monomer is selected from at least one of methyl methacrylate, butyl methacrylate, trimethylolpropane triacrylate (TMPTA), trimethylolpropane trimethacrylate (TMPTMA), and dipentaerythritol hexaacrylate (DPHA).
[0027] According to the embodiment of the present invention, in step 3), the purpose of cleaning with hydrophobic monomers is to replace the positive solvent in the zero-dimensional perovskite scintillator material on the one hand, and to prevent the zero-dimensional perovskite scintillator materials from sticking together on the other hand. Furthermore, the hydrophobic monomers can directly participate in the polymerization to prepare the zero-dimensional perovskite scintillator screen. Therefore, the cleaned wet zero-dimensional perovskite scintillator material can be used directly, avoiding the degradation of imaging quality caused by the adhesion of the zero-dimensional perovskite scintillator materials due to drying and other post-processing.
[0028] The present invention also provides zero-dimensional perovskite scintillator materials prepared by the above method.
[0029] According to an embodiment of the present invention, the particle size of the zero-dimensional perovskite scintillator material is 1-500 μm, for example, 1 μm, 10 μm, 20 μm, 50 μm, 80 μm, 100 μm, 150 μm, 200 μm, 250 μm, 300 μm, 350 μm, 400 μm, 450 μm or 500 μm.
[0030] According to an embodiment of the present invention, the zero-dimensional perovskite scintillator material contains polymerizable groups.
[0031] The present invention also provides a zero-dimensional perovskite scintillator screen, wherein the monomers for preparing the zero-dimensional perovskite scintillator screen include the above-mentioned zero-dimensional perovskite scintillator material.
[0032] According to an embodiment of the present invention, the monomers used to prepare the flickering screen further include hydrophobic monomers.
[0033] According to an embodiment of the present invention, the mass of the zero-dimensional perovskite scintillator material accounts for 10-50 wt% of the total mass of the hydrophobic monomer and the zero-dimensional perovskite scintillator material, for example, 10 wt%, 15 wt%, 20 wt%, 25 wt%, 30 wt%, 35 wt%, 40 wt%, 45 wt%, or 50 wt%.
[0034] According to an embodiment of the present invention, the raw materials for preparing the scintillator screen include zero-dimensional perovskite scintillator material, hydrophobic monomers, and photoinitiators.
[0035] According to an embodiment of the present invention, the mass of the photoinitiator accounts for 1-10 wt% of the total mass of the hydrophobic monomer and the photoinitiator, preferably 1.5-2.5 wt%, for example 1 wt%, 1.5 wt%, 2 wt%, 2.5 wt%, 3 wt%, 4 wt%, 5 wt%, 6 wt%, 7 wt%, 8 wt%, 9 wt%, or 10 wt%.
[0036] According to an embodiment of the present invention, the scintillator screen is prepared by copolymerizing zero-dimensional perovskite scintillator material and hydrophobic monomers under the initiation of a photoinitiator and under ultraviolet light irradiation.
[0037] According to an embodiment of the present invention, the hydrophobic monomer is selected from at least one of methyl methacrylate, butyl methacrylate, trimethylolpropane triacrylate (TMPTA), trimethylolpropane trimethacrylate (TMPTMA), and dipentaerythritol hexaacrylate (DPHA). Preferably, the hydrophobic monomer is a mixture of butyl methacrylate and trimethylolpropane triacrylate, and more preferably, the hydrophobic monomer is a mixture of butyl methacrylate and trimethylolpropane triacrylate in a volume ratio of (0.5-1.5):(0.5-1.5).
[0038] According to an embodiment of the present invention, the photoinitiator is selected from at least one of TPO, TPO-L, 819, 907 and ITX.
[0039] According to an embodiment of the present invention, the thickness of the flickering screen is 0.2-1.0 mm, for example, 0.2 mm, 0.3 mm, 0.4 mm, 0.5 mm, 0.6 mm, 0.7 mm, 0.8 mm, 0.9 mm or 1.0 mm.
[0040] According to an embodiment of the present invention, the scintillation screen can maintain its initial luminous intensity for 24 hours at a relative humidity of 0-85%; the scintillation screen can perform continuous X-ray imaging underwater for 24 hours.
[0041] The present invention also provides a method for preparing the above-mentioned zero-dimensional perovskite scintillator screen, comprising the following steps: a) Mix the hydrophobic monomer and the photoinitiator to obtain a protective solution; b) Mix the protective liquid from step a) with the zero-dimensional perovskite scintillator material to obtain a fluorescent layer slurry; c) First, the protective liquid from step a) is coated onto the substrate surface, and polymerization is carried out under ultraviolet light irradiation to obtain a substrate coated with a lower adhesion layer; then, a fluorescent layer slurry is coated onto the substrate coated with the lower adhesion layer, and polymerization is carried out under ultraviolet light irradiation to obtain a substrate coated with a lower adhesion layer and a fluorescent layer; then, the protective liquid is coated onto the substrate coated with the lower adhesion layer and the fluorescent layer, and polymerization is carried out under ultraviolet light irradiation to obtain a substrate coated with a lower adhesion layer, a fluorescent layer and an upper adhesion layer, thus preparing the zero-dimensional perovskite scintillator screen.
[0042] According to an embodiment of the present invention, in step a), the photoinitiator in the protective liquid accounts for 1-10 wt% of the total mass of the hydrophobic monomer and the photoinitiator, preferably 1.5-2.5 wt%, for example 1 wt%, 1.5 wt%, 2 wt%, 2.5 wt%, 3 wt%, 4 wt%, 5 wt%, 6 wt%, 7 wt%, 8 wt%, 9 wt%, or 10 wt%.
[0043] According to an embodiment of the present invention, in step b), the mass of the zero-dimensional perovskite scintillator material in the fluorescent layer slurry accounts for 10-50 wt% of the total mass of the hydrophobic monomer and the zero-dimensional perovskite scintillator material, for example, 10 wt%, 15 wt%, 20 wt%, 25 wt%, 30 wt%, 35 wt%, 40 wt%, 45 wt% or 50 wt%.
[0044] According to an embodiment of the present invention, in step c), the substrate is surface-treated glass; exemplarily, the surface treatment is plasma treatment or chemical treatment; the chemical treatment first involves immersing the glass in ammonia-hydrogen peroxide solution and hydrochloric acid-hydrogen peroxide hot solution in sequence, and then rinsing it with distilled water.
[0045] According to an embodiment of the present invention, the ammonia-hydrogen peroxide solution comprises concentrated ammonia, 30% hydrogen peroxide, and water, wherein the volume ratio of each component satisfies: concentrated ammonia: 30% hydrogen peroxide: water is (0.5-1.5): (0.5-1.5): (3-7); the hydrochloric acid-hydrogen peroxide solution comprises concentrated hydrochloric acid, 30% hydrogen peroxide, and water, wherein the volume ratio of each component satisfies: concentrated hydrochloric acid: 30% hydrogen peroxide: water is (0.5-1.5): (0.5-1.5): (4-8).
[0046] Preferably, the ammonia-hydrogen peroxide solution comprises concentrated ammonia, 30% hydrogen peroxide, and water, wherein the volume ratio of each component satisfies: concentrated ammonia: 30% hydrogen peroxide: water is (0.95-1.05): (0.95-1.05): (4.95-5.05); the hydrochloric acid-hydrogen peroxide solution comprises concentrated hydrochloric acid, 30% hydrogen peroxide, and water, wherein the volume ratio of each component satisfies: concentrated hydrochloric acid: 30% hydrogen peroxide: water is (0.95-1.05): (0.95-1.05): (5.95-6.05).
[0047] According to an embodiment of the present invention, the temperature of the ammonia-hydrogen peroxide solution is 60-70°C; the temperature of the hydrochloric acid-hydrogen peroxide solution is 70-80°C.
[0048] According to an embodiment of the present invention, the soaking time in ammonia-hydrogen peroxide solution is 5-30 minutes; the soaking time in hydrochloric acid-hydrogen peroxide hot solution is 5-30 minutes.
[0049] According to an embodiment of the present invention, in step c), the source of the ultraviolet light is not particularly limited, and can be ultraviolet light within a wavelength range known in the art; exemplaryly, the wavelength of the ultraviolet light is 200-400 nm, preferably 360-370 nm; the cumulative energy density of a single ultraviolet light irradiation is 1.5-6 J cm⁻¹. -2 For example, 1.5 J cm -2 2 J cm -2 2.5J cm -2 3 J cm -2 3.5 J cm -2 4 J cm -2 4.5 J cm -2 5 J cm -2 5.5 J cm -2 Or 6 J cm -2 The duration of a single irradiation with ultraviolet light is 5-30 minutes, preferably 7-12 minutes, for example, 5 minutes, 7 minutes, 8 minutes, 9 minutes, 10 minutes, 11 minutes, 12 minutes, 15 minutes, 16 minutes, 18 minutes, 20 minutes, 25 minutes, or 30 minutes.
[0050] According to an embodiment of the present invention, in step c), the coating amount of the protective liquid is 10-40 μL / cm. 2 For example, 10 μL / cm 2 15 μL / cm 2 20 μL / cm 2 25 μL / cm 2 30 μL / cm 235 μL / cm 2 or 40 μL / cm 2 The coating amount of the fluorescent layer slurry is 20-80 μL / cm. 2 For example, 20 μL / cm 2 25 μL / cm 2 30 μL / cm 2 35 μL / cm 2 40 μL / cm 2 45 μL / cm 2 50 μL / cm 2 55 μL / cm 2 60 μL / cm 2 65 μL / cm 2 70 μL / cm 2 75 μL / cm 2 Or 80 μL / cm 2 .
[0051] According to an embodiment of the present invention, in step c), the areas of the upper and lower adhesion layers formed by the protective liquid after ultraviolet light irradiation are both greater than the area of the fluorescent layer formed by the fluorescent layer slurry after ultraviolet light irradiation.
[0052] The present invention also provides a zero-dimensional perovskite scintillator screen prepared by the above method.
[0053] The present invention also provides the use of the above-mentioned zero-dimensional perovskite scintillation screen in high humidity environments or underwater X-ray imaging.
[0054] The beneficial effects of this invention are: The zero-dimensional perovskite scintillation screen provided by this invention anchors scintillator particles in a polymer matrix formed by hydrophobic monomers through chemical bonds, thereby increasing the water stability of the scintillation screen. This zero-dimensional perovskite scintillation screen solves the problem of unstable luminescence in humid environments. Compared to samples that only undergo physical mixing, the zero-dimensional perovskite scintillation screen of this invention can maintain its initial luminescence intensity unchanged for 24 hours at a relative humidity of 0-85%, and can perform continuous X-ray imaging underwater for 24 hours. This zero-dimensional perovskite scintillation screen provides stable luminescence and imaging in humid environments and underwater. Attached Figure Description
[0055] Figure 1 This is a single-crystal structure diagram of the MAc2MnBr2Cl2 scintillator powder prepared in Example 1.
[0056] Figure 2This is the Fourier transform infrared (FTIR) spectrum of the MAc2MnBr2Cl2 scintillator powder prepared in Example 1.
[0057] Figure 3 The emission and excitation spectra are those of the MAc2MnBr2Cl2 scintillator powder prepared in Example 1.
[0058] Figure 4 The fluorescence decay curve of the MAc2MnBr2Cl2 scintillator powder prepared in Example 1 in the 514 nm emission region is shown.
[0059] Figure 5 The image shows the radiative emission spectrum of the MAc2MnBr2Cl2 scintillator powder prepared in Example 1.
[0060] Figure 6 The image shows the Raman spectroscopic characterization of the perovskite-hydrophobic monomer copolymer imaging screen prepared in Example 1 before and after polymerization.
[0061] Figure 7 The image shows the FTIR spectroscopic characterization of the perovskite-hydrophobic monomer copolymer imaging screen prepared in Example 1 before and after polymerization.
[0062] Figure 8 This is a graph showing the fluorescence decay of the imaging screens prepared in Example 1 and Comparative Example 1 after being placed under conditions of 85% relative humidity for 24 hours.
[0063] Figure 9 The image is the result of continuous underwater X-ray imaging for 24 hours using the perovskite-hydrophobic monomer copolymer imaging screen prepared in Example 1. Detailed Implementation
[0064] The technical solution of the present invention will be further described in detail below with reference to specific embodiments. It should be understood that the following embodiments are merely illustrative and explanatory of the present invention, and should not be construed as limiting the scope of protection of the present invention. All technologies implemented based on the above content of the present invention are covered within the scope of protection intended by the present invention.
[0065] Unless otherwise specified, the experimental methods used in the following examples are conventional methods; unless otherwise specified, the reagents and materials used in the following examples are commercially available.
[0066] Example 1 A method for preparing a zero-dimensional scintillation screen with Mn(II)-based ions containing polymerizable groups at the A-site: 0.75 mol of MnBr2·4H2O was dissolved in 24 L of n-octanol to obtain a manganese bromide-n-octanol solution. 415.8 g of 75wt% methacryloyloxyethyltrimethylammonium chloride aqueous solution (containing 1.5 mol of methacryloyloxyethyltrimethylammonium) was added to the manganese bromide-n-octanol solution and stirred for 1 hour. During this process, a precipitate was formed. The precipitate was centrifuged and washed three times with butyl methacrylate. The precipitate was collected to obtain zero-dimensional perovskite scintillator powder MAc2MnBr2Cl2.
[0067] Take 1 L of butyl methacrylate, 1 L of trimethylolpropane triacrylate (TMPTA), and 40 g of photoinitiator 819, and stir thoroughly to obtain a protective solution; take 1 kg of the prepared wet scintillator powder (0.5 kg of dry scintillator powder and 0.5 kg of butyl methacrylate), add it to 1 L of the above-prepared protective solution, mix evenly, and obtain a fluorescent solution; A 63.5 cm × 63.5 cm glass substrate was treated for 10 minutes each with ammonia-hydrogen peroxide hot solution and hydrochloric acid-hydrogen peroxide hot solution, respectively. The solution ratios and temperatures were as follows: Ammonia-hydrogen peroxide solution: Concentrated ammonia: 30wt% hydrogen peroxide: water volume ratio of 1:1:5, temperature 65°C; Hydrochloric acid-hydrogen peroxide solution: concentrated hydrochloric acid: 30wt% hydrogen peroxide: water volume ratio of 1:1:6, temperature 75°C; After the treated glass substrate is washed with distilled water, it is dried with a clean airflow and set aside for later use. A protective solution was coated onto a glass substrate over a 63.5 cm × 63.5 cm area. The coated area was then irradiated with 365 nm ultraviolet light to form the lower adhesion layer, with a cumulative energy density of 3 J / cm². -2 ; 67.5 mL of fluorescent solution was coated onto the lower adhesion layer, with a coating area of 38.1 cm × 38.1 cm. The coated area was irradiated with 365 nm ultraviolet light, and the cumulative energy density was 3 J / cm². -2 A fluorescent layer is then formed.
[0068] A protective solution of 62.5 mL was applied to a 63.5 cm × 63.5 cm area on the fluorescent layer. The coated area was then irradiated with 365 nm UV light to form the lower adhesion layer, with a cumulative energy density of 3 J / cm². -2 A zero-dimensional perovskite scintillator screen was obtained.
[0069] Figure 1 This is a single-crystal structure diagram of the MAc2MnBr2Cl2 scintillator powder prepared in Example 1. From... Figure 1As can be seen, the A-site ion methacryloyloxyethyltrimethylammonium containing a C=C double bond is co-located with the tetracoordinated manganese halide anion MnBr2Cl2. 2- The crystals are arranged in an alternating pattern; among them, there are exposed C=C double bonds on the crystal surface, which provides the possibility for copolymerization to occur.
[0070] Figure 2 This is the Fourier transform infrared (FTIR) spectrum of the MAc2MnBr2Cl2 scintillator powder prepared in Example 1. From... Figure 2 As can be seen from the data, the A-site ions of the prepared MAc2MnBr2Cl2 scintillator powder contain polymerizable C=C double bonds.
[0071] Figure 3 These are the emission and excitation spectra of the MAc2MnBr2Cl2 scintillator powder prepared in Example 1. From... Figure 3 As can be seen, the sample exhibits three excitation regions at 250-300 nm, 350-400 nm, and 420-500 nm, and emits green light under 365 nm ultraviolet light excitation with a central wavelength of 514 nm, indicating that the emitting unit of the sample is [MnBr2Cl2]. 2- .
[0072] Figure 4 This is the fluorescence decay curve of the MAc2MnBr2Cl2 scintillator powder prepared in Example 1 in the 514 nm emission region. From... Figure 4 As can be seen, the sample luminescence is typical of [MnBr2Cl2]. 2- The luminescence of the dd transition.
[0073] Figure 5 This is the radiative emission spectrum of the MAc2MnBr2Cl2 scintillator powder prepared in Example 1. From... Figure 5 As can be seen, the luminescence center of the radiative emission is still [MnBr2Cl2]. 2- .
[0074] Figure 6 This describes the Raman spectral characterization of the zero-dimensional perovskite scintillation screen prepared in Example 1 before and after polymerization. Specifically, the fluorescent liquid prepared in Example 1 was coated onto the surface of the test substrate (glass slide), Raman characterization was performed first, then cured with a 365nm UV lamp for 5-10 minutes, and finally Raman characterization was performed on the cured fluorescent layer. Figure 6 As can be seen from the graph, compared with before polymerization (blue curve), after polymerization (orange curve), the C=C double bond vibration peak region (1640 cm⁻¹) is significantly higher. -1 The peak area (around 100°C) decreased significantly, indicating that polymerization did indeed occur.
[0075] Figure 7This describes the FTIR spectral characterization of the zero-dimensional perovskite scintillation screen prepared in Example 1 before and after polymerization. Specifically, the fluorescent liquid prepared in Example 1 was coated onto the surface of a test substrate (KBr pellet), first characterized using infrared spectroscopy, then cured with a 365nm UV lamp for 5-10 minutes, and finally characterized using infrared spectroscopy on the cured fluorescent layer. Figure 7 As can be seen, compared with before polymerization (blue curve), the transmittance at the unsaturated CH bond vibration peak increased after polymerization (orange curve), indicating that polymerization did indeed occur.
[0076] Figure 8 This is a graph showing the fluorescence decay of the scintillation screens prepared in Example 1 and Comparative Example 1 after being placed under conditions of 85% relative humidity for 24 hours. From... Figure 8 As can be seen from the data, compared with Comparative Example 1 which did not undergo copolymerization, the fluorescence intensity of Example 1 which underwent copolymerization decreased by only 2% of the initial intensity, indicating that copolymerization with the hydrophobic monomer increased the water resistance of the Mn(II)-based zero-dimensional perovskite scintillator.
[0077] Figure 9 This is the imaging result of continuous underwater X-ray imaging for 24 hours using the zero-dimensional perovskite scintillation screen prepared in Example 1. From Figure 9 As can be seen, after being submerged in water for 24 hours, the zero-dimensional perovskite scintillation screen can still perform clear X-ray imaging, indicating that the copolymerization strategy is indeed effective in improving the water resistance of the Mn(II)-based zero-dimensional perovskite scintillation screen.
[0078] Example 2 The preparation method in this embodiment is basically the same as that in Example 1, except that methacrylamide ethyltrimethylammonium chloride of the same concentration is used instead of methacryloyloxyethyltrimethylammonium chloride, while the other conditions remain unchanged.
[0079] Example 3 The preparation method in this embodiment is basically the same as that in Example 1, except that the same amount of MnCl2 is used to replace MnBr2·4H2O, while the other conditions remain unchanged.
[0080] Example 4 The preparation method in this embodiment is basically the same as that in Example 1, except that the same amount of MnI2 is used to replace MnBr2·4H2O, while the other conditions remain unchanged.
[0081] Example 5 The preparation method in this embodiment is basically the same as that in Example 1, except that 0.75 mol of MnBr2·4H2O is replaced with 0.5 mol of SbCl3, while the other conditions remain unchanged.
[0082] Example 6 The preparation method in this embodiment is basically the same as that in Example 1, except that 0.75 mol of MnBr2·4H2O is replaced with 0.5 mol of EuCl3, while the other conditions remain unchanged.
[0083] Example 7 The preparation method in this embodiment is basically the same as that in Example 1, except that the washing solvent is changed from butyl methacrylate to methyl methacrylate, while the other conditions remain unchanged.
[0084] Example 8 The preparation method in this embodiment is basically the same as that in Example 1, except that the washing solvent is changed from butyl methacrylate to methyl acrylate, while the other conditions remain unchanged.
[0085] Example 9 The preparation method of this embodiment is basically the same as that of Example 1, except that the trimethylolpropane triacrylate (TMPTA) in the protective solution is replaced with an equal volume of trimethylolpropane trimethacrylate (TMPTMA), while the other conditions remain unchanged.
[0086] Example 10 The preparation method of this embodiment is basically the same as that of Example 1, except that the volume ratio of butyl methacrylate and trimethylolpropane triacrylate in the protective solution is changed to 1:2, while the other conditions remain unchanged.
[0087] Example 11 The preparation method of this embodiment is basically the same as that of Example 1, except that the photoinitiator 819 in the protective solution is replaced with an equal mass of photoinitiator TPO, while the other conditions remain unchanged.
[0088] Example 12 The preparation method of this embodiment is basically the same as that of Example 1, except that the mass of photoinitiator 819 added to the protective solution is changed to 20 g, while the other conditions remain unchanged.
[0089] Example 13 The preparation method in this embodiment is basically the same as that in Example 1, except that the cumulative energy density of the irradiation is increased from 3 J / cm³. -2 Change to 6 J cm -2 All other conditions remain unchanged.
[0090] Comparative Example 1 A method for preparing a Mn(II)-based zero-dimensional perovskite scintillation screen with A-site ions lacking polymerizable groups: The preparation method of this comparative example is basically the same as that of Example 1. The difference is that the cationic salt that introduces the A-site ion (methacryloyloxyethyltrimethylammonium chloride) is replaced with benzyltrimethylammonium chloride (BTMACl), and the perovskite scintillator powder prepared is labeled as BTMA2MnBr2Cl2.
[0091] The embodiments of the present invention have been described above. However, the present invention is not limited to the above embodiments. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A zero-dimensional perovskite scintillator material, wherein, The general chemical formula of the scintillator material is: A m MX j ; Wherein, A is a cation containing polymerizable groups, and its structural formula is shown in Formula 1 below: Formula 1 In Formula 1, R1, R3, R4, and R5 may be the same or different, and are independently selected from hydrogen and alkyl groups; R2 is -O- or -NH-; n is 1, 2, or 3. X is any one or a combination of Cl, Br, and I; M is any one or a combination of Mn(II), Sb(III), Cd(II), Eu(III), Tb(III), Zn(II), and Zr(II); m and j are both positive integers, and m and j ensure the charge balance of the scintillator material.
2. The zero-dimensional perovskite scintillator material according to claim 1, wherein, m is an integer between 1 and 5, j is an integer between 3 and 7, and m and j ensure the charge balance of the scintillator material; And / or, in Equation 1, R1, R3, R4, and R5 may be the same or different, and are independently selected from hydrogen, C 1-5 alkyl; And / or, A is one of (alkyl)acrylamide ethyl trialkylammonium and (alkyl)acryloyloxy ethyl trialkylammonium, wherein the (alkyl)acrylamide ethyl trialkylammonium is selected from methacrylamide ethyl trimethylammonium; wherein the (alkyl)acryloyloxy ethyl trialkylammonium is selected from methacryloyloxy ethyl trimethylammonium.
3. The method for preparing the scintillator material according to claim 1 or 2, comprising the following steps: 1) Dissolve the metal halide salt in a normal solvent to obtain a metal halide salt solution; 2) Add the halide salt corresponding to the cation containing polymerizable groups to the above metal halide salt solution, and precipitate out to obtain a powdery precipitate; or, add the halide salt corresponding to the cation containing polymerizable groups to the above metal halide salt solution, and then add the antisolvent, and precipitate out to obtain a powdery precipitate. 3) The powder precipitate obtained in step 2) is washed with a hydrophobic monomer, centrifuged, and the lower powder solid is collected to obtain the scintillator material.
4. The preparation method according to claim 3, wherein, In step 1), the positive solvent is selected from at least one of methanol, ethanol, isopropanol, n-butanol, n-pentanol, isoamyl alcohol, n-hexanol, n-octanol, acetonitrile, dimethyl sulfoxide, and dimethylformamide; And / or, in step 1), the concentration of the metal halide salt solution is 10-50 mmol / L; And / or, in step 2), the halide salt corresponding to the cation containing polymerizable groups is preferably the chloride salt corresponding to the cation containing polymerizable groups; And / or, in step 2), the precipitation time is 0.5-5 hours; the precipitation temperature is room temperature; And / or, in step 2), the antisolvent is selected from anhydrous diethyl ether; And / or, in step 3), the hydrophobic monomer is selected from at least one of methyl methacrylate, butyl methacrylate, trimethylolpropane triacrylate (TMPTA), trimethylolpropane trimethacrylate (TMPTMA), and dipentaerythritol hexaacrylate (DPHA).
5. The zero-dimensional perovskite scintillator material prepared by the method of claim 3 or 4. Preferably, the particle size of the zero-dimensional perovskite scintillator material is 1-500 μm.
6. A zero-dimensional perovskite scintillator screen, wherein, The monomers used to prepare the zero-dimensional perovskite scintillator screen include the zero-dimensional perovskite scintillator material as described in claim 1, 2, or 5.
7. The zero-dimensional perovskite scintillator screen according to claim 6, wherein, The monomers used to prepare the flickering screen also include hydrophobic monomers. Preferably, the mass of the zero-dimensional perovskite scintillator material accounts for 10-50 wt% of the total mass of the hydrophobic monomer and the zero-dimensional perovskite scintillator material. Preferably, the raw materials for preparing the scintillator screen include zero-dimensional perovskite scintillator material, hydrophobic monomers, and photoinitiators. Preferably, the photoinitiator accounts for 1-10 wt% of the total mass of the hydrophobic monomer and the photoinitiator. Preferably, the hydrophobic monomer is selected from at least one of methyl methacrylate, butyl methacrylate, trimethylolpropane triacrylate (TMPTA), trimethylolpropane trimethacrylate (TMPTMA), and dipentaerythritol hexaacrylate (DPHA).
8. The method for preparing the zero-dimensional perovskite scintillator screen according to claim 6 or 7, comprising the following steps: a) Mix the hydrophobic monomer and the photoinitiator to obtain a protective solution; b) Mix the protective liquid from step a) with the zero-dimensional perovskite scintillator material to obtain a fluorescent layer slurry; c) First, the protective liquid from step a) is coated onto the substrate surface, and polymerization is carried out under ultraviolet light irradiation to obtain a substrate coated with a lower adhesion layer; then, a fluorescent layer slurry is coated onto the substrate coated with the lower adhesion layer, and polymerization is carried out under ultraviolet light irradiation to obtain a substrate coated with a lower adhesion layer and a fluorescent layer; then, the protective liquid is coated onto the substrate coated with the lower adhesion layer and the fluorescent layer, and polymerization is carried out under ultraviolet light irradiation to obtain a substrate coated with a lower adhesion layer, a fluorescent layer and an upper adhesion layer, thus preparing the zero-dimensional perovskite scintillator screen.
9. The preparation method according to claim 8, wherein, In step a), the photoinitiator in the protective liquid accounts for 1-10 wt% of the total mass of the hydrophobic monomer and the photoinitiator. And / or, in step b), the mass of the zero-dimensional perovskite scintillator material in the fluorescent layer slurry accounts for 10-50 wt% of the total mass of the hydrophobic monomer and the zero-dimensional perovskite scintillator material; And / or, in step c), the substrate is surface-treated glass; the surface treatment is plasma treatment or chemical treatment; And / or, in step c), the wavelength of the ultraviolet light is 200-400 nm; the cumulative energy density of a single ultraviolet light irradiation is 1.5-6 J cm⁻¹. -2 The duration of a single irradiation with the ultraviolet light is 5-30 minutes. And / or, in step c), the coating amount of the protective liquid is 10-40 μL / cm. 2 The coating amount of the fluorescent layer slurry is 20-80 μL / cm. 2 ; And / or, in step c), the areas of the upper and lower adhesion layers formed by the protective liquid after ultraviolet light irradiation are both greater than the area of the fluorescent layer slurry formed after ultraviolet light irradiation.
10. Use of the zero-dimensional perovskite scintillation screen according to claim 6 or 7 in high humidity environments or underwater X-ray imaging.